2013
DOI: 10.1002/ange.201308433
|View full text |Cite
|
Sign up to set email alerts
|

Silicium‐Sauerstoff‐Doppelbindungen: ein stabiles Silanon mit einem trigonal planar koordinierten Siliciumzentrum

Abstract: SiO im Komplex: Das erste bei Raumtemperatur stabile Silanon, 3, wird in zwei Stufen durch Carbonylierung des Silylidinkomplexes 1 zum Chromiosilylen 2 und anschließende Oxidation mit N2O erhalten. Silanon 3 enthält eine kurze polare Si‐O‐Doppelbindung (1.526(3) Å) zu einem trigonal‐planar koordinierten Siliciumzentrum und reagiert mit Wasser unter Bildung eines Dihydroxysilylkomplexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 68 publications
2
41
0
1
Order By: Relevance
“…In the 29 Si NMR spectrum, ab road quartet signal appears at significantly downfield (71.3 ppm) compared with donor-stabilized silanones (À55 to À91 ppm) [7][8][9][10][11] or the previously reported (amino)(ylide)silanones VI (39. Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent. Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…In the 29 Si NMR spectrum, ab road quartet signal appears at significantly downfield (71.3 ppm) compared with donor-stabilized silanones (À55 to À91 ppm) [7][8][9][10][11] or the previously reported (amino)(ylide)silanones VI (39. Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent. Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent.…”
mentioning
confidence: 75%
“…Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent. This value,i ng ood agreement with the DFT calculated n (Si=O (1128 cm À1 ), is red-shifted compared to those observed for IV (1157 cm À1 ), [13] V (1150 cm À1 ), [14] and Me 2 Si = O(1204 cm À1 in an argon matrix), [2b] which is probably due to the presence of strongly p-donating substituents attached to the silanone. [16] The 11 BNMR resonance is shifted upfield at d = À24.3 ppm (J PB = 190.2 Hz) relative to that of silylene 1 (15.3 ppm), [15] suggesting ad ecreased p-interaction between bora-ylide function and the silicon center.The IR spectroscopy of 2 shows asignal at 1130 cm À1 in C 6 D 6 which was assigned to the Si=O stretching.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…[15][16][17][18][19] Furthermore,i th as been clearly established that the nature of the substituents (electronegativity, s-donating ability, bulkiness etc.) [20] Nevertheless,t he choice of substituents is still largely restricted to main-group-based substituents and, surprisingly, IX is the only example of at ransition-metalsubstituted stable silylene described to date, [21,22] even though such a-metalated species could lead to ad ramatically increased variation of the substituents.I ndeed, the types and coordination number of the ligands,which often crucially characterize the electronic nature of am etal center, should greatly affect the properties of the corresponding a-metalated silylene.T hus,F ilippou et al have demonstrated that silylene IX,w hich features aC r ÀSi single bond, can be transformed into the Cr Si-bonded species X,j ust by removing aC O ligand. [20] Nevertheless,t he choice of substituents is still largely restricted to main-group-based substituents and, surprisingly, IX is the only example of at ransition-metalsubstituted stable silylene described to date, [21,22] even though such a-metalated species could lead to ad ramatically increased variation of the substituents.I ndeed, the types and coordination number of the ligands,which often crucially characterize the electronic nature of am etal center, should greatly affect the properties of the corresponding a-metalated silylene.T hus,F ilippou et al have demonstrated that silylene IX,w hich features aC r ÀSi single bond, can be transformed into the Cr Si-bonded species X,j ust by removing aC O ligand.…”
mentioning
confidence: 99%